Semilinear Volterra Integrodifferential Problems with Fractional Derivatives in the Nonlinearities - Mokhtar Kirane; Milan Medveď; Nasser-eddine Tatar (Abstract and Applied Analysis)
A second-order semilinear Volterra integrodifferential equation involving fractional time derivatives is considered. We prove existence and uniqueness of mild solutions and classical solutions in appropriate spaces.